Deficiency of the Two-Pore-Domain Potassium (K2P) Channel TREK-1 Promotes Hyperoxia-Induced Lung Injury - Schwingshackl, Andreas (2014)
OBJECTIVE: We previously reported the expression of the 2-pore domain K(+) channel TREK-1 in lung epithelial cells and proposed a role for this channel in the regulation of alveolar epithelial cytokine secretion. In this study we focused on investigating the role of TREK-1 in vivo in the development of hyperoxia-induced lung injury. DESIGN: Laboratory animal experiments. SETTING: University research laboratory. SUBJECTS: Wild type and TREK-1 deficient mice. INTERVENTIONS: Mice were anesthetized and exposed to 1) room air, no mechanical ventilation, 2) 95% hyperoxia for 24 hours, 3) 95% hyperoxia for 24 hours followed by mechanical ventilation for 4 hours. MEASUREMENTS AND MAIN RESULTS: Hyperoxia exposure accentuated lung injury in TREK-1 deficient mice but not controls, resulting in increased in Lung Injury Scores (LIS), broncho-alveolar lavage (BAL) fluid cell numbers and cellular apoptosis, and a decrease in quasi-static lung compliance. Exposure to a combination of hyperoxia and injurious mechanical ventilation resulted in further morphological lung damage, increased LIS and BAL fluid cell numbers in control but not TREK-1 deficient mice. At baseline and after hyperoxia exposure BAL cytokine levels were unchanged in TREK-1 deficient mice compared to controls. Exposure to hyperoxia and mechanical ventilation resulted in an increase in BAL IL-6, MCP-1 and TNF-α levels in both mouse types, but the increase in IL-6 and MCP-1 levels was less prominent in TREK-1 deficient mice than in controls. Lung tissue MIP-2, KC and IL-1β gene expression was not altered by hyperoxia in TREK-1 deficient mice compared to controls. Furthermore, we show for the first time TREK-1 expression on alveolar macrophages and unimpaired TNF-α secretion from TREK-1 deficient macrophages. CONCLUSION: TREK-1 deficiency resulted in increased sensitivity of lungs to hyperoxia but this effect is less prominent if overwhelming injury is induced by the combination of hyperoxia and injurious mechanical ventilation. TREK-1 may constitute a new potential target for the development of novel treatment strategies against hyperoxia-induced lung injury.